Apa Peran Jarak Kekuasaan Dalam Hubungan Antara Kepemimpinan Dan Perilaku Ekstra Warga Organisasi? - Subiyanto, Didik; Susanto (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
The extra role of employees will have a very significant impact on the good or bad of the organization. If the extra role of employees is high, it will be an advantage for the organization, and vice versa. The purpose of this study was to examine in depth the role of Transformational Leadership and Transactional Leadership in Organizations Citizenship Behavior (OCB), by involving Power Distance as moderation. The sample was taken as many as 65 employees from the hotel industry in the Special Region of Yogyakarta who were randomly assigned using the FormsApp.. The collected data were processed using the SPSS program. The processed data has met the data quality requirements. The results of the study provide an explanation that Transformational Leadership has a significant positive effect on Organizational Citizenship Behavior (OCB), while Transactional Leadership has been empirically confirmed to have a positive effect on a weak level of significance on Organizational Citizenship Behavior (OCB). Furthermore, the analysis results show that Power Distance as a moderating variable weakens the influence of Transformational Leadership and Transactional Leadership on Organizational Citizenship Behavior. The implication of the results of this study provides a clear picture where if there are human resource management practices that create a wider distance between superiors and subordinates, it will have a negative impact on organizational performance because of the low extra roles that employees have. Therefore the results of this study can provide information and strategic direction in human resource management in an effort to increase the extra role of employees.